Biodiversity of a red clover collection based on morpho-productive traits - Radinović Irena; Vasiljević Sanja; Branković Gordana; Živanović Tomislav; Prodanović Slaven (Acta Agriculturae Serbica, 2022)
Red clover (Trifolium pratense L.) is a meadow and pasture species in natural habitats and also a cultivated species used for animal nutrition. The aim of this research was the assessment of the diversity of 46 red clover accessions based on morpho-productive traits. The traits were investigated according to the UPOV descriptors for red clover-number of internodes, number of branches, stem length, stem thickness, middle leaflet length, middle leaflet width, green matter yield and dry matter yield. The principal components analysis (PCA) explained 74% of the variance of the standardized data and showed relationships between 46 red clover accessions and eight morpho-productive traits, associations among traits and performance of accessions. Among the determined Euclidean distances, the smallest value was obtained for the accessions Rotra and Titus (0.048), the largest value was 1.099 for a pair of NCPGRU2 and Čortanovci accessions, and the average value was 0.380. Two clusters of 46 red clover accessions were separated in the dendrogram based upon UPGMA (Unweighted Pair-Group Method with Arithmetic mean) for eight morpho-productive traits. The first cluster included two subclusters, while the second cluster contained four subclusters. The grouping of the accessions from the red clover collection by the UPGMA cluster analysis can be linked to the geographical origin of the accessions: central and Southern Europe for three subclusters and northeastern Europe for one subcluster.